Primary retrograde intrarenal surgery versus excorporeal shockwave lithotripsy in high risk renal stones - Ab. Rashid, Islah Munjih; Wahi, Aisah; Ghazali, Hamid (Mary Ann Liebert, Inc., 2017)
Introduction & Objective: Incidence of urolithiasis is high in our country. Treatment modalities vary depending to the size and location of stone and patient's fitness for invasive treatment. Identifying the most suitable treatment modalities according to patient's clinical characteristic is important to get optimum stone clearance with least complication and better cost-benefit.